Hypertension in Malaysia: An Analysis of Trends From the National Surveys 1996 to 2011. Issue 2 (January 2016) - Naing, Cho; Yeoh, Peng Nam; Wai, Victor Nyunt; Win, Ni Ni; Kuan, Lai Pei; Aung, Kyan
Abstract : Abstract: This study aimed to determine trends in prevalence, awareness, and control of hypertension in Malaysia and to assess the relationship between socioeconomic determinants and prevalence of hypertension in Malaysia. The distribution of hypertension in Malaysia was assessed based on available data in 3 National Health and Morbidity Surveys (NHMSs) and 1 large scale non-NHMS during the period of 1996 to 2011. Summary statistics was used to characterize the included surveys. Differences in prevalence, awareness, and control of hypertension between any 2 surveys were expressed as ratios. To assess the independent associations between the predictors and the outcome variables, regression analyses were employed with prevalence of hypertension as an outcome variable. Overall, there was a rising trend in the prevalence of hypertension in adults ≥30 years: 32.9% (30%–35.8%) in 1996, 42.6% (37.5%–43.5%) in 2006, and 43.5% (40.4%–46.6%) in 2011. There were significant increase of 32% from 1996 to 2011 ( P < 0.001) and of 29% from 1996 to 2006 ( P < 0.05), but only a small change of 1% from 2006 to 2011 ( P = 0.6). For population ≥18 years, only a 1% increase in prevalence of hypertension occurred from the 2006 NHMS (32.2%) to the 2011 NHMS (32.7%) ( P = 0.25). A relative increase of 13% occurred in those with primary education ( P < 0.001) and a 15% increase was seen in those with secondary education ( P < 0.001). The rate of increase in the prevalence of hypertension in the population with income level RM 3000–3999 was the highest (18%) during this period. In general, the older age group had higher prevalence of hypertension in the 2006 and 2011 NHMSs. The prevalence peaked at 74.1% among population aged 65 to 69 years in the 2011 NHMS. Both the proportion of awareness and the control of hypertension in Malaysia improved from 1996 to 2006. A change in the control of hypertension was 13% higher in women than in men. The findings suggest that the magnitude of hypertension in Malaysia needs additional attention. Strengthening the screening for hypertension in primary health-care settings in the high-risk groups and frequent health promotion to the community to enhance individual awareness and commitment to healthy living would be of immense value.